Computed Tomography–Guided Percutaneous Gastrostomy/Jejunostomy for Feeding and Decompression. (21st June 2016) - Albrecht, Heinz; Hagel, Alexander F.; Schlechtweg, Philipp; Foertsch, Thomas; Neurath, Markus F.; Mudter, Jonas
Abstract : Background: An effective method for long‐term enteral feeding or stomach decompression is the use of a percutaneous gastrostomy (PEG) or sometimes jejunostomy (PEJ). Under certain circumstances (eg, inadequate transillumination), endoscopic placement of PEG/PEJ tubes is impossible. In these cases, computed tomography (CT)–guided PEG/PEJ may represent an alternative technique. In this study, we evaluate indications, results, and complications of CT‐guided PEG/PEJ. Materials and Methods: A total of 102 consecutive referred patients were enrolled in the study. Patients came to the endoscopy unit of our department to undergo a CT‐guided PEG/PEJ for long‐term intragastric/intrajejunal feeding (n = 57) or decompression (n = 45). The majority (n = 98) received a pull‐through PEG/PEJ with simultaneous gastroscopy/jejunoscopy. Dose length product and the effective dose for every patient were calculated. Results: PEG/PEJ tube placement was successful in 87.3% (89 of 102). Feeding PEG/PEJ tube placement was successfully completed in 91.2% (52 of 57); decompressive PEG/PEJ tube placement was likewise successfully completed in 82.2% (37 of 45). No procedure‐related mortality was observed. Minor complications (eg, tube dysfunction, local bleeding, minimal leakage, local skin infection) were observed in 13 patients. The complication rate was similar between the feeding and decompression groups ( P = .9). Conclusions: CT‐guided PEG/PEJ is a feasible and safe method with a low procedure‐related morbidity rate for patients where endoscopic placement via transillumination is not successful. Thus, the procedure is an attractive alternative to surgical tube placement. Long‐term complications, mainly tube disturbances, can be treated easily.